Porphyria Cutanea Tarda Presenting as Erythema-multiforme Like Lesions - Parajuli, Niraj; Jha, Harendra Kumar; Jonkman, Marcel F (Journal of Nepal Health Research Council, 2019)
Porphyria cutaneatarda, is the most common type of porphyria.It is characterized by defective uroporphyrinogen III decarboxylase enzyme.It presents with erosion, bulla with milia formation and sometimes with hypertrichosis and abnormal pigmentation mostly on the photo-exposed sites. A urine fluorescence of coral red color helps in the diagnosis. Here, we present a rare case of porphyria cutanea tarda in a 15 years old male who presented with multiple targetoid plaques.Keywords: Erythema-multiforme; porphyria cutanea tarda; targetoid.